The Role of Socioeconomic Status in EFL Learning Strategies - Ahsanah, Finaty; Dias Tiara Putri Utomo; Ririn Indah Prastiwi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the relationship between students’ socioeconomic status (SES) and their use of language learning strategies (LLSs) within an English as a Foreign Language (EFL) context. Using Oxford’s (1990) taxonomy of language learning strategies as a framework, the study involved 46 sixth-semester students majoring in hospital administration enrolled in an Intensive English Class. Employing a quantitative research design, data were collected through a modified and translated version of the Strategy Inventory for Language Learning (SILL) questionnaire. The data were analyzed using the Statistical Package for the Social Sciences (SPSS), with the Pearson correlation test applied to determine the relationship between SES and LLS use. The results showed no statistically significant correlation between socioeconomic status and language learning strategies, indicating that students from different SES backgrounds use strategies with similar frequency and types. These findings suggest that language learning strategies are likely influenced more by internal learner factors—such as motivation, cognitive preferences, or instructional context—than by socioeconomic status. The study highlights the importance of providing equitable language learning support and recommends further research into possible mediating variables that may affect strategic learning behavior.